Acetylcholinesterase inhibition and antifungal activity of cyclohexanoids from the endophytic fungus Saccharicola sp. - Chapla, Vanessa M. (2020)
Three new oxygenated cyclohexanoids, namely, speciosin U (1), speciosin V (2) and speciosin W (3), along with four known compounds consisting of 4-hydroxy-3-(3′-methylbut-3′-en-1′-ynyl)-benzoic acid (4), 4-hydroxy-3-prenyl-benzoic acid (5), 2,2-dimethyl-2H-chromene-6-carboxylic acid (6) and trans-3,4-dihydro-3,4-dihydroxy-anofinic acid (7) were isolated from scale-up cultures of Saccharicola sp., an endophyte of Eugenia jambolana. The structures were established by analysis of spectroscopic data, including 1D and 2D NMR. The absolute configuration of 1 was determined using Mosher's method. Speciosin U (1) and trans-3,4-dihydro-3,4-dihydroxy-anofinic acid (7) exhibited a potent acetylcholinesterase (AChE) inhibitory activity comparable to reference inhibitor galantamine. Furthermore, speciosin U (1) presented antifungal activity invitro against the phytopathogenic fungi Cladosporium cladosporioides, while compounds 4-hydroxy-3-(3′-methylbut-3′-en-1′-ynyl)-benzoic acid (4) and 4-hydroxy-3-prenyl-benzoic acid (5) exhibited antifungal activity against C. sphaerospermum.